2005
DOI: 10.1055/s-2005-873153
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Stable Treatment Response in Patients with Major Depression Treated with Hypericum Extract WS® 5570/5572

Abstract: A substantial fraction of the patients treated with Hypericum extracts WS(R) 5570/5572 showed a meaningful reduction of depressive symptoms during the first two weeks of treatment (early improvement), which was found to be a sensitive predictor of sustained response. The results determined for the herbal extracts were comparable to those for effective synthetic antidepressants investigated previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…This observation points to an antidepressant-like effect of these dimeric acylphloroglucinols, which can represent a new chemical scaffold related to antidepressant activity. It is also important to note that 1 and 8 exhibit dimeric structures consisting of an acylphloroglucinol moiety and an acylfilicinic acid-type ring that differs from hyperforin, which exhibits a bicyclononane skeleton with several isoprene chains . Structural differences between 1 and 8 and hyperforin could be especially relevant since the latter has been considered to be responsible for serious drug interactions, which restrict the clinical use of H. perforatum .…”
Section: Resultsmentioning
confidence: 99%
“…This observation points to an antidepressant-like effect of these dimeric acylphloroglucinols, which can represent a new chemical scaffold related to antidepressant activity. It is also important to note that 1 and 8 exhibit dimeric structures consisting of an acylphloroglucinol moiety and an acylfilicinic acid-type ring that differs from hyperforin, which exhibits a bicyclononane skeleton with several isoprene chains . Structural differences between 1 and 8 and hyperforin could be especially relevant since the latter has been considered to be responsible for serious drug interactions, which restrict the clinical use of H. perforatum .…”
Section: Resultsmentioning
confidence: 99%
“…Szegedi et al (2003) found early improvement, defined as a score reduction of > 20% on the HAM-D within 2 weeks, to be a highly sensitive predictor of later stable response or stable remission. Kieser and Szegedi (2005) using 20% improvement on the HAM-D to predict a sustained 50% decrease, found a high sensitivity (87%) and low specificity (43%) in week 2 and the opposite in week 1 (43 and 86% respectively). However, another study found that patients unimproved (less than 25% improvement in the HAM-D score) at week 6, had a remission rate at week 12 of 31% using an intention to treat analysis, or 41% using a completers analysis (Quitkin et al, 2003).…”
Section: Introductionmentioning
confidence: 88%
“…In addition, the majority of the published studies mentioned above are either open studies (Nierenberg et al, 2000;Quitkin et al, 2003) or combined results from more than 1 RCT (Kieser and Szegedi, 2005;Sackeim et al, 2005;Mulsant et al, 2006). As a result of this, there is no 'gold standard' to predict final remission.…”
Section: Introductionmentioning
confidence: 90%
“…Several studies have found encouraging evidence that response and/or remission may be predicted as early as 1–4 weeks into treatment, based on initial response, with a variety of standard antidepressant agents and herbal remedies such as St John’s wort, as well as cognitive behavioral therapy (Coryell et al, 1982; Quitkin et al, 1984; Downing et al, 1985; Stassen et al, 1993; Nierenberg et al, 1995, 2000; Bech, 2001; Kieser et al, 2005; Szegedi et al, 2003, 2009; Henkel et al, 2009; Wade et al, 2009; Nakajima et al, 2010; Tadic et al, 2010). …”
Section: Introductionmentioning
confidence: 99%